Mepitel Film and Mepilex Lite for the prophylaxis and treatment of skin toxicities from breast radiation. (August 2019) - Wan, Bo Angela; Chan, Stephanie; Herst, Patries; Yee, Caitlin; Popovic, Marko; Lee, Justin; Lam, Henry; Pon, Kucy; Aljabri, Saleh; Soliman, Hany; Wronski, Matt; Chow, Edward
Abstract: Despite the prevalence of radiation dermatitis in breast cancer patients, current practice guidelines for its treatment are limited. We aimed to discuss the quality of evidence for the barrier-forming Mepitel Film for prophylaxis of radiation dermatitis, and argue for further investigation into evidence-based management of skin toxicities. Two studies assessing Mepitel Film were critically evaluated. Both reported that Mepitel Film decreased radiation dermatitis; moreover, patient-reported outcomes significantly favoured Mepitel Film. However, there has not been global adoption of barrier-forming films such as Mepitel, in part due to the absence of multi-centred randomised trials and the heterogeneity of study designs.